Rights in the face of biometric systems incorporating Artificial Intelligence - Garriga Domínguez, Ana (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Starting from an approach based on the risks that the processing of biometric data and biometric AI systems imply for human rights, the protection of human rights is analysed in the legislation on the protection of personal data and in the Proposal for a Regulation on Artificial Intelligence of the European Union.